Electrochemical recycling of recycled concrete powder: Selective recovery of calcium and silica to enable sustainable construction materials - Zheng Fang; Guangqi Xiong; Zongxuan Shao; Shuai Zhou; Guangfeng Ou; Lei Liu; Michio Suzuki; Chong Wang; Yuya Sakai (Resources, Environment and Sustainability)
Rapid urbanization produces billions of tons of concrete waste annually, with recycled concrete powder (RCP) posing significant challenges due to its high porosity and limited reusability. To overcome RCP’s inherent limitations and maximize resource utilization, we developed a novel “Recycled Concrete Powder Electrolyzer” for selective recovery of key components. This electrochemical method efficiently extracted Ca2＋ ions from RCP, achieving a 96% calcium extraction efficiency comparable to acid leaching. The process produced high-purity portlandite (94% purity; 65.58% yield) with crystal sizes below 30μm, ideal for cement manufacturing, while also recovering fine sand powder and silica-containing products. A Ca(NO3)2 electrolyte enhanced Ca2＋ migration and prevented membrane fouling, resulting in lower energy consumption compared to the NaNO3 system. By converting RCP into a carbon-free cement precursor and recovering valuable components, this approach demonstrates the feasibility of transforming problematic waste into sustainable construction materials. It offers a circular economy solution for concrete waste recycling, reducing landfill burden while providing a low-emission alternative for cement production.